A nanofiber felt with nonlinear volt-ampere characteristic, an epoxy resin composite material and a preparation method thereof
Patent Information
- Application Number
- CN202411459968.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-10-18
AI Technical Summary
[0005]本发明的目的之一在于避免现有技术的不足而提供一种具有非线性伏安特性的纳米纤维毡,利用不同费米能级金属氧化物半导体掺杂的方法合成了具有较高肖特基势垒的纳米纤维,解决无渗流阈值复合材料非线性伏安特性能不理想的问题
[0034] (1) The nanofiber felt with nonlinear current-voltage characteristics provided in this application does not affect the nonlinear current-voltage characteristics of the nanofibers when the polarity is reversed, and the threshold field strength change does not exceed 2V/mm. The nonlinear coefficient of the nanofiber felt, the nonlinear coefficient of tungsten trioxide and gallium trioxide at different doping concentrations are all greater than 10, and it has a stable double Schottky barrier. The nonlinear current-voltage characteristics are not affected by the randomness of the nanofiber arrangement.
Smart Images

Figure CN119411314B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of electrical and electronic insulation materials technology, and in particular to a nanofiber felt with nonlinear current-voltage characteristics, an epoxy resin composite material, and a preparation method thereof. Background Technology
[0002] Polymer dielectrics, with their high voltage resistance and ease of processing, have become crucial packaging materials for high-power devices such as electronic products, 5G-6G high-frequency communication substrates, spacecraft, and high-voltage converters. However, with increasing power density and integration, traditional insulating materials struggle to adapt to the electric field distortions caused by partial discharge or charge accumulation in electrical and electronic devices.
[0003] Related research has found that smart dielectrics capable of adaptively controlling their electrical parameters have been shown to effectively release unwanted charge to avoid overvoltage. However, for SiC-filled smart dielectric materials, due to the relatively low Schottky barrier formed at the interface between the contacting SiC fillers, even with a large amount of filler, excellent nonlinear current-voltage characteristics cannot be obtained. Furthermore, although ZnO-filled micro-varistors are designed to have high double Schottky barriers within each particle and exhibit good nonlinear performance, their random distribution and high percolation threshold still require a large amount of filler, resulting in a lack of nonlinear stability. High doping rates also directly increase the processing difficulty of the composite material and reduce its mechanical properties. Therefore, excellent nonlinear current-voltage performance and low doping rates in composite materials are often mutually exclusive. How to balance excellent nonlinear performance and adaptive charge dissipation performance is a key research focus for polymer dielectrics.
[0004] This section provides only background information relevant to this application and is not necessarily prior art. Summary of the Invention
[0005] One of the objectives of this invention is to overcome the shortcomings of existing technologies and provide a nanofiber felt with nonlinear current-voltage characteristics. Nanofibers with high Schottky barriers are synthesized by using a method of doping metal oxide semiconductors with different Fermi levels, thus solving the problem of unsatisfactory nonlinear current-voltage performance of composite materials without percolation threshold.
[0006] The second objective of this invention is to provide a method for preparing nanofiber mats with nonlinear current-voltage characteristics.
[0007] The third objective of this invention is to provide a method for preparing epoxy resin composite materials.
[0008] The fourth objective of this invention is to provide an epoxy resin composite material.
[0009] One of the objectives of this invention is achieved through the following technical solution:
[0010] A nanofiber felt with nonlinear current-voltage characteristics is provided. The nanofiber felt is formed by non-directional stacking of nanofibers to form a three-dimensional porous network structure. The nanofibers are assembled from silicon carbide, tungsten trioxide, and gallium trioxide.
[0011] The second objective of this invention is achieved through the following technical solution:
[0012] A method for preparing the above-mentioned nanofiber mat with nonlinear current-voltage characteristics is provided, comprising the following steps:
[0013] (1) Polycarbosilane, polyethylene oxide and gallium acetylacetonate were mixed and dissolved in chloroform, and then nano-tungsten trioxide was added and mixed evenly to obtain a mixed dispersion.
[0014] (2) The mixed dispersion is electrospun to obtain nanopolymer fiber felt, which is then wound and assembled and then cured and pyrolyzed to obtain silicon carbide-doped gallium trioxide and tungsten trioxide nanofiber felt.
[0015] In some embodiments, in step (1), the ratio of the amount of polycarbosilane, polyethylene oxide, gallium acetylacetonate and nano-tungsten trioxide added is 1g:(0.12-0.36g):(8-15mL):(0.03-0.09g).
[0016] In some embodiments, in step (2), the solution insertion rate of electrospinning is set to 200 mm / s, the applied voltage is 60 kV, the collector distance is 24 mm, the curing temperature is 200 °C, and the curing time is 5 h.
[0017] In some implementations, in step (2), pyrolysis specifically involves:
[0018] Under the protection of an inert gas, the solidified material is pyrolyzed at a temperature of 1300℃, with a heating rate of 1℃ / min.
[0019] The third objective of this invention is achieved through the following technical solution:
[0020] A method for preparing an epoxy resin composite material is provided, the method comprising:
[0021] The epoxy resin matrix, curing agent and accelerator are mixed evenly to obtain an epoxy resin mixture. Then, the nanofiber felt is immersed in the epoxy resin mixture. The epoxy resin-impregnated nanofiber felt is taken out and subjected to vacuum drying and curing treatment to obtain an epoxy resin composite material.
[0022] The nanofiber felt is the nanofiber felt with nonlinear volt-ampere characteristics described above or the nanofiber felt with nonlinear volt-ampere characteristics obtained by the above preparation method.
[0023] In some embodiments, the volume fraction of the nanofiber felt is 0.3% to 2% of the epoxy resin composite material.
[0024] In some embodiments, the epoxy resin matrix includes at least one of bisphenol A type epoxy resin, alicyclic epoxy resin, and biphenyl type epoxy resin;
[0025] The curing agent is methylhexahydrophthalic anhydride or methyltetrahydrophthalic anhydride;
[0026] The accelerator includes at least one of DMP30, triethylamine, and 2-ethyl-4-methylimidazole;
[0027] The component ratio of the epoxy resin matrix, curing agent and accelerator is 100:(70-120):(0.1-1).
[0028] In some embodiments, the vacuum drying process is carried out at a temperature of 70°C for 12 hours.
[0029] The curing process specifically includes:
[0030] The first stage of curing treatment, the second stage of curing treatment, and the third stage of curing treatment are performed sequentially. The curing temperature of the first stage of curing treatment is 105℃ and the curing time is 1 hour; the curing temperature of the second stage of curing treatment is 115℃ and the curing time is 1 hour; and the curing temperature of the third stage of curing treatment is 135℃ and the curing time is 1 hour.
[0031] The fourth objective of this invention is achieved through the following technical solution:
[0032] An epoxy resin composite material is provided, which is prepared by the above-described method.
[0033] The technical solution provided in this application may include the following beneficial effects:
[0034] (1) The nanofiber felt with nonlinear current-voltage characteristics provided in this application does not affect the nonlinear current-voltage characteristics of the nanofibers when the polarity is reversed, and the threshold field strength change does not exceed 2V / mm. The nonlinear coefficient of the nanofiber felt, the nonlinear coefficient of tungsten trioxide and gallium trioxide at different doping concentrations are all greater than 10, and it has a stable double Schottky barrier. The nonlinear current-voltage characteristics are not affected by the randomness of the nanofiber arrangement.
[0035] (2) The nanofiber felt with nonlinear current-voltage characteristics provided in this application solves the problem that nonlinear current-voltage characteristics and low doping rate are often mutually exclusive. While maintaining excellent nonlinear performance and charge adaptive dissipation performance, it can also significantly reduce the volume fraction of nanofiber felt in epoxy resin composite materials.
[0036] (3) The method for preparing nanofiber felt with nonlinear current-voltage characteristics provided in this application involves electrospinning a mixed solution of polycarbosilane, polyethylene oxide, gallium acetylacetonate, and nano-tungsten trioxide, and obtaining a nanofiber felt with a three-dimensional structure through non-directional stacking. The randomness of the nanofiber arrangement does not affect its own nonlinear current-voltage characteristics. It has a stable double Schottky barrier, which can improve the insulation level of high-voltage electrical equipment and regulate the spatial electric field distribution of high-voltage electrical equipment, thus ensuring the safe and stable operation of electrical equipment.
[0037] (4) The preparation method of the epoxy resin composite material provided in this application is simple and can be used for industrial production.
[0038] (5) The epoxy resin composite material provided in this application, with a nanofiber felt filling amount of 0.3%, achieves excellent nonlinear current-voltage characteristics of epoxy resin composite material through its own continuous percolation path and aspect ratio. The ratio of tungsten to gallium in nanofiber felt does not affect the nonlinear current-voltage characteristics of epoxy resin composite material. Attached Figure Description
[0039] The above and other objects, features and advantages of this application will become more apparent from the more detailed description of exemplary embodiments of this application taken in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of this application.
[0040] Figure 1 Transmission electron microscopy image, elemental mapping diagram, X-ray diffraction pattern and X-ray photoelectron spectroscopy diagram of the nanofiber mat prepared in Example 1;
[0041] Figure 2 Atomic force microscopy images of the nanofiber mat prepared in Example 1 and nonlinear voltammetric characteristic test diagrams of the nanofiber mats prepared in Examples 1 to 5;
[0042] Figure 3 SEM image of the epoxy resin composite material prepared in Example 6;
[0043] Figure 4 The nonlinear current-voltage characteristic curves of the epoxy resin composites prepared in Examples 6 to 13 are shown. Detailed Implementation
[0044] Preferred embodiments of the present application will now be described in more detail with reference to the accompanying drawings. While preferred embodiments of the present application are shown in the drawings, it should be understood that the present application may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0045] Improving the insulation level of high-voltage electrical equipment and regulating the spatial electric field distribution are among the core issues in the research and development and manufacturing of advanced electrical equipment. Developing intelligent insulation materials that can adapt to complex service environments and achieve adaptive matching between their electrical properties and external electric fields to effectively regulate the uniformity of the electric field is of great significance for the development of advanced electrical materials and the safe and stable operation of electrical equipment.
[0046] To address the above problems, this invention provides a nanofiber felt, an epoxy resin composite material with nonlinear volt-ampere characteristics, and a preparation method thereof.
[0047] The present invention will be further described in detail below with reference to the embodiments. There are no special restrictions on the source of all raw materials used in the present invention. They can be purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0048] There are no particular restrictions on the purity of any raw materials used in this invention. However, it is preferred to use analytical grade or conventional purity used in the field of resin materials.
[0049] In a typical embodiment of the present invention, a nanofiber felt with nonlinear current-voltage characteristics is provided. Nanofibers with high Schottky barriers are synthesized by using a method of doping metal oxide semiconductors with different Fermi levels, which solves the problem of non-ideal nonlinear coefficient of composite materials without percolation threshold and effectively improves the nonlinear current-voltage performance of nanofibers.
[0050] In one embodiment of the present invention, a nanofiber felt with nonlinear current-voltage characteristics is provided. The nanofiber felt is a three-dimensional porous network structure formed by non-directional stacking of nanofibers, wherein the nanofibers are assembled from silicon carbide, tungsten trioxide, and gallium trioxide.
[0051] While researching high-voltage electrical equipment, the inventors discovered that nanofibers made from silicon carbide, tungsten trioxide, and gallium trioxide through electrospinning, which are then wound and assembled into non-oriented nanofiber mats, are combined with epoxy resin. Experimental results show that the epoxy resin composite material, through the continuous percolation path of the nanofiber mats and the extremely high aspect ratio of the nanofibers, exhibits excellent nonlinear current-voltage characteristics even at a filling amount of 0.3 vol%. Furthermore, the threshold field strength gradually decreases with increasing filling volume fraction. Moreover, at the same volume fraction of nanofiber mats, different proportions of tungsten and gallium in the epoxy resin composite material result in similar threshold field strengths. This indicates that when the volume fraction of nanofiber mats in the epoxy resin composite material is the same, the threshold field strength is positively correlated with the total mass fraction of the doped metal oxide semiconductor, while the proportion of tungsten and gallium has a relatively small impact.
[0052] In another embodiment of the present invention, a method for preparing a nanofiber mat with nonlinear voltammetric characteristics is provided, the method comprising:
[0053] (1) Polycarbosilane, polyethylene oxide and gallium acetylacetonate were mixed and dissolved in chloroform, and then nano-tungsten trioxide was added and mixed evenly to obtain a mixed dispersion.
[0054] (2) The mixed dispersion is electrospun to obtain nanopolymer fiber felt, which is then wound and assembled and then cured and pyrolyzed to obtain silicon carbide-doped gallium trioxide and tungsten trioxide nanofiber felt.
[0055] Furthermore, in step (1) of the above-mentioned method for preparing nanofiber mats with nonlinear voltammetric characteristics, the ratio of the amount of polycarbosilane, polyethylene oxide, gallium acetylacetonate and nano-tungsten trioxide added is 1g:(0.12~0.36g):(8~15mL):(0.03~0.09g).
[0056] The electrospinning method described in this invention can be any method well known to those skilled in the art and is not particularly limited. The solution insertion rate of the electrospinning is set to 120–280 mm / s, preferably 150–250 mm / s, more preferably 180–220 mm / s; the applied voltage for electrospinning is 55–65 kV, preferably 58–63 kV, more preferably 60 kV; the collector distance is 20–30 mm, preferably 22–28 mm, more preferably 24–26 mm; the curing temperature of the electrospinning is 150–250 °C, preferably 180–220 °C, more preferably 200 °C; and the curing time of the electrospinning is 3–7 h, preferably 4–6 h, more preferably 5 h.
[0057] Furthermore, in step (2) of the above-mentioned method for preparing nanofiber felt with nonlinear volt-ampere characteristics, the pyrolysis specifically involves:
[0058] Under the protection of an inert gas, the solidified material is pyrolyzed at a temperature of 1300℃, with a heating rate of 1℃ / min.
[0059] In another embodiment of the present invention, a method for preparing an epoxy resin composite material is provided, the method comprising:
[0060] The epoxy resin matrix, curing agent and accelerator are mixed evenly to obtain an epoxy resin mixture. Then, the nanofiber felt is immersed in the epoxy resin mixture. The epoxy resin-impregnated nanofiber felt is taken out and subjected to vacuum drying and curing treatment to obtain an epoxy resin composite material.
[0061] The nanofiber felt is the nanofiber felt with nonlinear volt-ampere characteristics described above or the nanofiber felt with nonlinear volt-ampere characteristics obtained by the above preparation method.
[0062] This invention does not impose any particular limitations on epoxy resin, curing agent, and accelerator. Any epoxy resin known to those skilled in the art, as well as epoxy resin curing agents and accelerators, can be used. These can be prepared using conventional methods or purchased commercially.
[0063] The epoxy resin of this invention includes any one or a combination of at least two of bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenolic epoxy resin, brominated epoxy resin, alicyclic epoxy resin, and biphenyl type epoxy resin. Typical but non-limiting examples of such combinations include: a combination of bisphenol A type epoxy resin and bisphenol F type epoxy resin, a combination of bisphenol F type epoxy resin and phenolic epoxy resin, a combination of phenolic epoxy resin and brominated epoxy resin, a combination of brominated epoxy resin and bisphenol A type epoxy resin, or a combination of bisphenol A type epoxy resin, bisphenol F type epoxy resin, and phenolic epoxy resin, etc.
[0064] The curing agent of this invention preferably includes one or more of polyamide 300, polyamide 2004, 4-diaminodiphenylmethane, methylhexahydrophthalic anhydride, or methyltetrahydrophthalic anhydride, more preferably polyamide 300, methylhexahydrophthalic anhydride, or methyltetrahydrophthalic anhydride, and more specifically preferably methylhexahydrophthalic anhydride. This invention does not impose any particular limitation on the amount of curing agent added. To improve dispersion and composite material performance, the mass ratio of the curing agent to the epoxy resin is preferably 100:(70-120), more preferably 100:(80-100), even more preferably 100:(90-95), and most preferably 100:(92-95).
[0065] The accelerator described in this invention preferably includes one or more of DMP30, triethylamine, and 2-ethyl-4-methylimidazole, more preferably DMP30 and triethylamine, and more specifically triethylamine. The mass ratio of the accelerator to the epoxy resin is preferably 100:(0.1-1), more preferably 100:(0.3-0.6).
[0066] In this invention, the volume fraction of the nanofiber felt with nonlinear volt-ampere characteristics is 0.2% to 5% of the epoxy resin composite material, more preferably 0.25% to 3% of the epoxy resin composite material, and more specifically, the volume fraction of the nanofiber felt is 0.3% to 2% of the epoxy resin composite material.
[0067] Specifically, the product of the reaction of polycarbosilane, polyethylene oxide, and gallium acetylacetonate nano-tungsten trioxide is subjected to electrospinning treatment, and the obtained nanopolymer fiber felt is wound and assembled. In this invention, the volume fraction of nanofiber felt in epoxy resin is determined by adjusting the number of winding layers of nanofiber felt. The more layers wound, the larger the winding volume, and correspondingly, the larger the volume fraction of nanofiber felt.
[0068] The mixing method described in this invention is preferably heating and stirring. This invention does not impose any particular restrictions on the conditions for heating and stirring; any stirring and mixing conditions well-known to those skilled in the art are acceptable. Those skilled in the art can select and adjust the conditions according to actual production conditions, product requirements, and quality requirements. The heating temperature described in this invention is preferably 40–65°C, more preferably 50–60°C. The stirring time described in this invention is preferably 15–30 minutes, more preferably 17–27 minutes, and most preferably 20–25 minutes. The stirring speed is preferably 1000–2000 r / min, more preferably 1200–1800 r / min, and most preferably 1400–1600 r / min.
[0069] The immersion described in this invention refers to completely submerging the nanofiber felt in the epoxy resin mixture. To improve dispersion and composite material performance, after the nanofiber felt is completely submerged in the epoxy resin mixture, the container containing the epoxy resin mixture can be placed in a vacuum chamber for vacuum treatment to remove air bubbles from the epoxy resin mixture. The vacuum treatment pressure is 0.01-0.07 MPa, more preferably 0.02-0.06 MPa, and most preferably 0.03-0.05 MPa.
[0070] The present invention describes the removal of the epoxy resin-impregnated nanofiber felt, specifically by removing the nanofiber felt after a certain period of immersion. Those skilled in the art can select the immersion time of the nanofiber felt based on the type of epoxy resin, curing agent, and accelerator, as well as the curing agent of the curing agent. The immersion time described in the present invention is preferably 15 to 30 minutes, more preferably 17 to 27 minutes, and most preferably 20 to 25 minutes.
[0071] Furthermore, the vacuum drying temperature of the above-mentioned epoxy resin composite material preparation method is 70°C, and the vacuuming time is 12 hours.
[0072] The curing process specifically includes:
[0073] The first stage of curing treatment, the second stage of curing treatment, and the third stage of curing treatment are performed sequentially. The curing temperature of the first stage of curing treatment is 105℃ and the curing time is 1 hour; the curing temperature of the second stage of curing treatment is 115℃ and the curing time is 1 hour; and the curing temperature of the third stage of curing treatment is 135℃ and the curing time is 1 hour.
[0074] To further illustrate the present invention, the following detailed description of the nanofiber felt with nonlinear voltammetric characteristics, epoxy resin composite material, and preparation method provided by the present invention is provided in conjunction with embodiments. However, it should be understood that these embodiments are implemented under the premise of the technical solution of the present invention, and provide detailed implementation methods and specific operating procedures, only to further illustrate the features and advantages of the present invention, and not to limit the claims of the present invention. The scope of protection of the present invention is not limited to the following embodiments.
[0075] Furthermore, the epoxy resin composite material prepared by the above steps in this invention can be specifically named EP / SiC-Ga. x W y In this composite material, EP represents epoxy resin, SiC represents silicon carbide, Ga represents gallium, x represents the mass fraction of gallium in the total mass of the nanofiber felt, W represents tungsten, and y represents the mass fraction of tungsten in the total mass of the nanofiber felt. When x and y are determined, the mass fraction of SiC is also determined. During testing, the EP / SiC-Ga composite material was obtained through transmission electron microscopy (TEM), elemental mapping, X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). x W y The values of X and Y in the above EP / SiC-Ga... require special explanation. x W y This is for reference only and does not imply that the epoxy resin composite material with the above component ratio can necessarily be obtained by preparing it according to the preparation method of this invention.
[0076] Example 1: Preparation of SiC-Ga 10 W 10Nanofiber felt:
[0077] 1. Using 1g of polycarbosilane, 0.24g of polyethylene oxide and 10mL of gallium acetylacetonate as precursors, the mixture was stirred evenly in chloroform at room temperature with a magnetic stirrer to obtain a dispersion.
[0078] 2. Add 0.03g of nano-tungsten trioxide to the dispersion and transfer it to a high-end ultrasonic disperser for ultrasonic dispersion to obtain a mixed dispersion;
[0079] 3. The mixed dispersion was transferred to an electrospinning machine for high-voltage electrospinning. The solution insertion rate of the electrospinning was set to 200 mm / s, the applied voltage was 60 kV, the collector distance was 24 mm, the curing temperature was 200℃, and the curing time was 5 h to obtain polymer nanofiber felt. After winding and assembly, it was cured at high temperature in an air oven.
[0080] 4. The cured nanofiber felt was transferred to a high-temperature tube furnace and pyrolyzed at 1300℃ under the protection of argon atmosphere. The pyrolysis heating rate was 1℃ / min to obtain SiC-based nanofiber felt doped with metal oxide semiconductors Ga2O3 and WO3.
[0081] Among them, SIC-Ga 10 W 10 The mass fraction of silicon carbide (SiC) is 80%, the mass fraction of gallium (Ga) is 10%, and the mass fraction of tungsten (W) is 10%.
[0082] Example 2: Preparation of SiC-Ga 10 W 15 Nanofiber felt:
[0083] With the preparation of SiC-Ga 10 W 10 The difference with nanofiber felt is that the amount of nano-tungsten trioxide added is 0.045g.
[0084] Example 3: Preparation of SiC-Ga 10 W 20 Nanofiber felt:
[0085] With the preparation of SiC-Ga 10 W 10 The difference with nanofiber felt is that the amount of nano-tungsten trioxide added is 0.06g.
[0086] Example 4: Preparation of SiC-Ga 15 W 10 Nanofiber felt:
[0087] With the preparation of SiC-Ga 10 W10 The difference with nanofiber felt is that the amount of gallium acetylacetone added is 15 mL.
[0088] Example 5: Preparation of SiC-Ga 15 W 15 Nanofiber felt:
[0089] With the preparation of SiC-Ga 10 W 10 The difference with nanofiber felt is that the amount of gallium acetylacetonate added is 15 mL, and the amount of nano tungsten trioxide added is 0.045 g.
[0090] This application also addresses the aforementioned SIC-Ga 10 W 10 The nanofiber felt underwent TEM testing, elemental distribution analysis, XRD analysis, and W 4f spectrum analysis, as detailed in [link to details]. Figure 1 .
[0091] Depend on Figure 1 It can be seen that among them Figure 1 Nanofibers with a high aspect ratio and uniform diameter of approximately 100 nm were observed. Elemental mapping revealed that the nanofibers contained abundant Si, C, O, and Ga elements, and W was also clearly visible. Figure 1 b).
[0092] To further characterize the crystal and molecular structure of the nanofibers, X-ray diffraction was used to observe the crystal structure of the nanofiber mat, such as... Figure 1 As shown in c, the strong diffraction peaks at 36.3° and 73.5° correspond to the (111) and (311) crystal planes of SiC, respectively, while the diffraction peaks at 32°, 48.9°, 64.6°, and 77.5° correspond to the (104), (024), (214), and (217) crystal planes of Ga2O3, respectively (refer to XRD standard card: 01-074-1610). The diffraction peaks of WO3 are weaker, with only a slight diffraction peak at 41°, corresponding to the (222) crystal plane (refer to XRD standard card: 01-024-0747). This is due to the small particle size (20 nm) and low content of nano-WO3 particles.
[0093] XPS was used to further characterize the elemental composition of the nanofiber felt and the valence state of W, such as... Figure 1 d and Figure 1 As shown in e, the full spectrum reveals spectral peaks for each orbital of the five elements: Si, C, O, Ga, and W. Combined with XRD results, the spectrum indicates the presence of three compounds: SiC, Ga₂O₃, and WO₃. However, the characteristic peak of the W 4f orbital is masked by the strong characteristic peaks of other elements. Therefore, the characteristic peak of the 4f orbital is locally magnified, as shown in... Figure 1As shown in e.
[0094] W4f splits and unrotates into a twofold state with binding energy peaks of 34.8 eV and 36.8 eV, corresponding to W4f, respectively. 7 / 2 and W4f 5 / 2 Two atomic states, this belongs to W 6+ The oxidation state also reveals the existence of WO3.
[0095] This application performed AFM testing on the nanofiber mat prepared in Example 1, and also performed radial voltammetric characteristic testing on the nanofiber mats prepared in the above examples, as detailed in the following figures. Figure 2 See Table 1.
[0096] When performing AFM testing on nanofiber mats, the nanofiber mats are uniformly dispersed on a conductive substrate. Under an atomic force microscope, individual nanofibers that are not in contact with the surrounding substrate are identified. Then, using conductive atomic force microscopy mode, a conductive probe is moved to directly contact the nanofibers. The scanning images and test principle diagram are shown below. Figure 2 As shown in Figure a, the probe is connected to a DC source and an ammeter, with a tip radius of 25 nm and a length of approximately 10-15 μm. Finally, the nonlinear current-voltage characteristics of a single nanofiber were tested by applying a scanning voltage with a scanning frequency of 0.5 Hz. The uniformity and stability were verified by testing the nonlinear current-voltage characteristics of the nanofiber under positive and negative bias voltages, respectively. The results are shown in Figure a. Figure 2 b and Table 1 are shown. From Figure 2 As shown in b, the volt-ampere characteristics of the nanofiber felts in all embodiments exhibit similar variation patterns, and the varistor voltage decreases significantly with increasing Ga2O3 or WO3 doping concentration. Notably, the nonlinear coefficients of the nanofibers are all greater than 10 at different GaW doping concentrations. A comparison of the nonlinear characteristic parameters after applying positive and negative biases in Table 1 shows that polarity reversal has almost no effect on the nonlinear volt-ampere characteristics of the nanofiber felts; the threshold field strength change does not exceed 2V / mm, and the nonlinear coefficient is relatively stable. This indicates that the synthesized nanofiber felts have uniform Ga2O3 and WO3 doping, possess a stable double Schottky barrier, and their nonlinear volt-ampere characteristics are unaffected by the randomness of fiber arrangement.
[0097] Table 1. Nonlinear coefficients and threshold field strength of nanofiber mats
[0098]
[0099]
[0100] Example 6:
[0101] (1) Stir 100 parts by weight of bisphenol A type epoxy resin, 70 parts by weight of methyltetrahydrophthalic anhydride and 0.5 parts by weight of triethylamine at 60°C for 30 minutes.
[0102] (2) The SiC-Ga from Example 5 15 W 15 The nanofiber felt was immersed in the epoxy resin mixture until it was completely penetrated. The mixture was then transferred to a high-temperature vacuum drying oven and continuously evacuated at a temperature of 70°C for 12 hours until no more bubbles appeared.
[0103] (3) The nanofiber felt completely impregnated with epoxy resin was removed and transferred to a stainless steel mold. It was cured at 105°C for 1 hour, then at 115°C for 1 hour, and finally at 135°C for 1 hour to prepare a nanofiber felt containing 0.3 vol% SiC-Ga. 15 W 15 Epoxy resin composite materials.
[0104] Example 7
[0105] The difference from Example 6 is that a SiC-Ga content of 0.5 vol% was prepared. 15 W 15 Epoxy resin composite materials.
[0106] Example 8
[0107] The difference from Example 6 is that a SiC-Ga content of 1 vol% was prepared. 15 W 15 Epoxy resin composite materials.
[0108] Example 9
[0109] The difference from Example 6 is that a SiC-Ga content of 2 vol% was prepared. 15 W 15 Epoxy resin composite materials.
[0110] Example 10
[0111] The difference from Example 6 is that the SiC-Ga prepared in Example 3 was used instead of Example 3. 10 W 20 Nanofiber mats were impregnated in an epoxy resin mixture to prepare a product containing 0.3 vol% SiC-Ga. 15 W 15 Epoxy resin composite materials.
[0112] Example 11
[0113] The difference from Example 10 is that a SiC-Ga content of 0.5 vol% was prepared. 15 W 15 Epoxy resin composite materials.
[0114] Example 12
[0115] The difference from Example 10 is that a SiC-Ga content of 1 vol% was prepared. 15 W 15 Epoxy resin composite materials.
[0116] Example 13
[0117] The difference from Example 10 is that a SiC-Ga content of 2 vol% was prepared. 15 W 15 Epoxy resin composite materials.
[0118] This application performed SEM tests on the epoxy resin composite material prepared in Example 6, and analyzed the nonlinear coefficient and threshold field strength of the epoxy resin composite materials prepared in Examples 6 to 13. The SEM tests are shown in [see attached image]. Figure 3 Nonlinear coefficients and threshold field strength are seen Figure 4 And Table 2.
[0119] Table 2 Nonlinear coefficients and threshold field strengths for Examples 6 to 13
[0120]
[0121] When performing SEM testing on the epoxy resin composite material prepared in Example 6, a field emission scanning electron microscope was used to characterize the epoxy resin composite material containing nanofiber mats. To facilitate clear observation of the nanofibers on the surface of the composite material, a laser ablation machine was used to etch the epoxy resin on the material surface, thereby exposing the arrangement of the nanofibers on the surface of the composite material, such as... Figure 3 As shown, coiled nanofibers are clearly visible on the material surface, with a well-cured epoxy resin matrix filling the spaces between the fibers, and no obvious interface defects are observed. Figure 3 It is evident that the nanofibers composed of tungsten oxide, gallium trioxide, and silicon carbide form a closely connected linear conduction path. Therefore, when local electric field inhomogeneity occurs, leading to partial discharge, they can serve as a complete charge release path and rapidly conduct and release the charge along the arrangement direction.
[0122] To investigate the effect of epoxy resin composites filled with nanofiber mats of different volume fractions on nonlinear volt-ampere characteristics, the effects of EP / SiC-Ga composites filled with different volume fractions of nanofiber mats were compared at 0.3 vol%, 0.5 vol%, 1 vol%, and 2 vol%. 15 W 15 and EP / SiC-Ga 10 W 20 The nonlinear current-voltage characteristics of composite materials, such as Figure 4As shown in Table 2, the results indicate that the epoxy resin composite material with extremely low filler content (0.3 vol%) exhibits excellent nonlinear voltammetric characteristics, which is attributed to the continuous flow path of the nanofiber felt and the extremely high aspect ratio of the nanofibers. The threshold field strength gradually decreases with increasing filler volume fraction. However, at the same volume fraction, the EP / SiC-Ga... 15 W 15 and EP / SiC-Ga 10 W 20 The similar threshold field strength of the composite materials indicates that when the volume fraction of the nanofiber felt is the same, the threshold field strength is related to the total mass fraction of the doped metal oxide semiconductor. Furthermore, Table 2 shows that the nonlinear coefficient of the composite material is around 10 for all filler volume fractions, indicating that this epoxy resin composite material has extremely high nonlinear stability and can meet the requirements for a uniform electric field in power transmission and transformation equipment.
[0123] The various embodiments of this application have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or improvement of the technology in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.
Claims
1. A method for preparing a nanofiber mat with nonlinear voltammetric characteristics, characterized in that, The preparation method includes: (1) Polycarbosilane, polyethylene oxide and gallium acetylacetonate were mixed and dissolved in chloroform, and then nano-tungsten trioxide was added and mixed evenly to obtain a mixed dispersion. (2) Electrospinning the mixed dispersion liquid to obtain nanopolymer fiber felt, which is then cured and pyrolyzed after winding and assembly to obtain silicon carbide-doped gallium trioxide and tungsten trioxide nanofiber felt. The nanofiber felt forms a three-dimensional porous network structure by non-directional stacking of nanofibers, which are assembled from silicon carbide, tungsten trioxide, and gallium trioxide.
2. The method for preparing nanofiber mats with nonlinear volt-ampere characteristics according to claim 1, characterized in that, In step (1), the amounts of polycarbosilane, polyethylene oxide, gallium acetylacetonate, and nano-tungsten trioxide added are as follows: based on 1g of polycarbosilane, 0.12~0.36g of polyethylene oxide, 8~15mL of gallium acetylacetonate, and 0.03~0.09g of nano-tungsten trioxide.
3. The method for preparing nanofiber mats with nonlinear volt-ampere characteristics according to claim 2, characterized in that, In step (2), pyrolysis specifically involves: Under the protection of an inert gas, the solidified material is pyrolyzed at a temperature of 1300℃, with a heating rate of 1℃ / min.
4. A method for preparing an epoxy resin composite material, characterized in that, The preparation method includes: The epoxy resin matrix, curing agent and accelerator are mixed evenly to obtain an epoxy resin mixture. Then, the nanofiber felt is immersed in the epoxy resin mixture. The epoxy resin-impregnated nanofiber felt is taken out and subjected to vacuum drying and curing treatment to obtain an epoxy resin composite material. The nanofiber felt is a nanofiber felt with nonlinear volt-ampere characteristics obtained by the preparation method according to any one of claims 1 to 3.
5. The method for preparing the epoxy resin composite material according to claim 4, characterized in that, The volume fraction of the nanofiber felt is 0.3% to 2% of the epoxy resin composite material.
6. The method for preparing the epoxy resin composite material according to claim 5, characterized in that, The epoxy resin matrix includes at least one of bisphenol A type epoxy resin, alicyclic epoxy resin and biphenyl type epoxy resin; The curing agent is methylhexahydrophthalic anhydride or methyltetrahydrophthalic anhydride; The accelerator includes at least one of DMP30, triethylamine, and 2-ethyl-4-methylimidazole; The component ratio of the epoxy resin matrix, curing agent and accelerator is 100:(70~120):(0.1~1).
7. The method for preparing the epoxy resin composite material according to claim 4, characterized in that, The vacuum drying process is carried out at a temperature of 70°C for 12 hours. The curing process specifically includes: The first stage of curing treatment, the second stage of curing treatment, and the third stage of curing treatment are performed sequentially. The curing temperature of the first stage of curing treatment is 105℃ and the curing time is 1 hour; the curing temperature of the second stage of curing treatment is 115℃ and the curing time is 1 hour; and the curing temperature of the third stage of curing treatment is 135℃ and the curing time is 1 hour.
8. An epoxy resin composite material, prepared using the preparation method of the epoxy resin composite material according to any one of claims 4 to 7.
Citation Information
Patent Citations
Quantum dot betavoltaic battery
WO2019113842A1